Iridium-catalyzed C4-alkylation of 2,6-di-tert-butylphenol by using hydrogen-borrowing catalysis - Frost, J; Cheong, C; Donohoe, T (Thieme, 2016)
An iridium-catalyzed hydrogen borrowing process has been developed whereby 2,6-di-tert-butylphenol can be alkylated at the C4-position using a range of different primary alcohols (11 examples, 40–93% yield). Following this, a selection of the products obtained underwent retroFriedel–Crafts reaction to provide para-substituted phenols which could potentially undergo further synthetic manipulation.